Rational design of common transition metal-nitrogen-carbon catalysts for oxygen reduction reaction in fuel cells. (December 2016) - Zheng, Yongping; Yang, Dae-Soo; Kweun, Joshua M.; Li, Chenzhe; Tan, Kui; Kong, Fantai; Liang, Chaoping; Chabal, Yves J.; Kim, Yoon Young; Cho, Maenghyo; Yu, Jong-Sung; Cho, Kyeongjae
Abstract: Bio-inspired non-precious-metal catalysts based on iron and cobalt porphyrins are promising alternatives to replace costly platinum-based catalysts for oxygen reduction reaction (ORR) in fuel cells. However, the exact nature of the active sites is still not clearly understood, and further optimization design is needed for practical applications. Here, we report a rational catalyst design process by combining density functional theory (DFT) calculations and experimental validations. Two sets of square-planar (MNx C4−x ) and square-pyramid (MNx C5−x ) active centers (M=Mn, Fe, Co, Ni) incorporated in graphene were examined using DFT. Fe-N5 and Co-N4 sites were identified theoretically to have the best performance in fuel cells, while Ni-Nx C4−x sites catalyze the most H2 O2 byproduct. Graphene samples with well-dispersed incorporations of metals were synthesized, and the following electrochemical measurements show an excellent agreement with the theoretical predictions, indicating that a successful design framework and systematic understanding toward the catalytic nature of these materials are established. Graphical abstract: Highlights: Graphene based catalysts design for ORR is demonstrated by combining experiments and modellings. Iron porphyrin like active site is unraveled to be five nitrogen coordinated as FeN5 . Cobalt porphyrin like active site is shown to be four nitrogen coordinated as CoN4 . Nickel porphyrin like catalyst is potentially used for catalytic synthesis of H2 O2 .